Festival Economy: The Impact of Events on Sustainable Tourism - Purwadi Purwadi; Dio Darma; Made Setini (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
Tourism is like a “treasure” and needs to be developed in order to attract visitors to an area. The advantage of those who have a destination with the presence of various attractions, events, and local culture considered a bonus. The case study of the tourism sector in Samarinda City has not yet developed and is in line with expectations, therefore we have started aspects of the festival economic which are expanded into three dimensions (event management, sustainable tourism, and destination branding). Evaluation to find out how big its role is, filtered by multiple regression analysis. We collected the data based on surveys, in which it conducted direct interviews with respondents who had a good understanding of the local demographic, social and cultural conditions. The survey coverage has determined based on time and place considerations, so they aimed specifically it at the two-day “The 354th Anniversary of Samarinda City” in 2022. The outcome of this study concludes that event management has a significant effect on sustainable tourism and destination branding. In line with that, we also found that sustainable tourism has a significant effect on destination branding and sustainable tourism can play a significant role in both the relationship between event management and destination branding, because the results are significant. Further, our need to study to enrich our findings so that the novelty will continue. The novelty of the theoretical or practical landscape teaches about market segmentation in the middle of a transition, especially boosting tourism commodities towards new trends.